2022
DOI: 10.3389/fphar.2022.816347
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Taohong Siwu Decoction on the Prevention and Treatment of Myocardial Injury

Abstract: Taohong Siwu decoction (THSWD) is one of the classic prescriptions for promoting blood circulation and removing blood stasis. With the continuous in-depth excavation in basic and clinical research, it has been found that THSWD has made greater progress in the prevention and treatment of cardiovascular diseases. Mechanisms of the current studies have shown that it could prevent and treat the myocardial injury by inhibiting inflammatory reaction, antioxidant stress, inhibiting platelet aggregation, prolonging cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…These mechanisms make it a potential treatment option for preventing and treating myocardial injury. [54] Given its positive therapeutic effect on atherosclerosis and the interrelation between atherosclerosis and DVT, investigating whether THSWD can simultaneously inhibit The PI3K/Akt signaling pathway plays a critical role in numerous physiological and pathological processes, including cell growth, differentiation, and proliferation. [55] Research has shown that the FXII protein can promote the occurrence of deep vein thrombosis (DVT) by inducing an inflammatory response and activating the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms make it a potential treatment option for preventing and treating myocardial injury. [54] Given its positive therapeutic effect on atherosclerosis and the interrelation between atherosclerosis and DVT, investigating whether THSWD can simultaneously inhibit The PI3K/Akt signaling pathway plays a critical role in numerous physiological and pathological processes, including cell growth, differentiation, and proliferation. [55] Research has shown that the FXII protein can promote the occurrence of deep vein thrombosis (DVT) by inducing an inflammatory response and activating the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[32,33] THSWD, a well-known Chinese herbal medicine for promoting blood circulation and removing blood stasis, is frequently used in clinical practice to prevent blood stasis in fractures or during the early postoperative period. [34,35] The ingredients Chuanxiong, Angelica, Baishao, Rehmannia glutinosa, Peach kernel, and Safflower in the formula can dilate blood vessels. [36] The primary component of safflower is crocin, which inhibits platelet aggregation and reduces blood coagulation function, ultimately decreasing thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also has anti‐platelet aggregation effects and protects the vascular endothelium 20 . Recent studies used Gualou Xiebai Banxia Decoction to treat 31 cases of chronic heart failure of coronary heart disease with phlegm rubidium‐blocked qi stagnation and blood stasis, with satisfactory clinical efficacy and a total effective rate of 90.3% 21 . Another study treated 226 patients with stable angina pectoris and type‐2 diabetes by trichosanthis peel injection and found that angina pectoris symptoms and hemorheology indices in the experimental group were significantly improved 21 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent studies used Gualou Xiebai Banxia Decoction to treat 31 cases of chronic heart failure of coronary heart disease with phlegm rubidium-blocked qi stagnation and blood stasis, with satisfactory clinical efficacy and a total effective rate of 90.3%. 21 Another study treated 226 patients with stable angina pectoris and type-2 diabetes by trichosanthis peel injection and found that angina pectoris symptoms and hemorheology indices in the experimental group were significantly improved. 21 Moreover, the protective effect of trichosanthis peel was found on acute myocardial ischemia in rats, and decoction of trichosanthis peel had a significant protective effect on acute myocardial ischemia in rats, while its mechanism may be related to enhancing the ability to scavenge free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation